Positive association between advanced lung cancer inflammation index and gallstones, with greater impact on women: a cross-sectional study of the NHANES database - Liu, Bailiang; Jin, Luyuan; Nan, Boyuan; Sun, Zhongyi; Chen, Fengyang; Zhou, Yinghui; Sa, Qila; Feng, Yingnan; Men, Ao; Wang, Wenxin; Feng, Xiaodong; Zhang, Wei (Frontiers in Nutrition, 2024)
BackgroundPrevious studies have shown that inflammation is crucial in gallstone formation. The Advanced Lung Cancer Inflammation Index (ALI) is a comprehensive measure that reflects inflammation and nutritional condition. However, there are no studies examining the relationship between ALI and gallstones. This study aimed to analyze this association in US adults.MethodsThis study used a cross-sectional research design with in-depth analyses using data from the National Health and Nutrition Examination Survey (NHANES). The association between gallstones and ALI was systematically assessed by logistic regression analysis, subgroup analysis, basic participant characteristics, and smooth curve fits.Results5,646 people participated in the study. ALI was converted into Quartile 1 (−1.47–1.00), Quartile 2 (1.00–1.34), Quartile 3 (1.34–1.69), and Quartile 4 (1.69–4.38). In the fully adjusted model, gallstone prevalence increased by 45% in participants in the highest quartile compared to those in the lowest quartile (OR = 1.45; 95% CI: 1.12–1.87; p = 0.005), and ALI was positively correlated with gallstones (OR = 1.22; 95% CI: 1.03–1.45; p = 0.0232). Smooth curve fits provided evidence in favor of this finding. Significant gender differences were found in the relationship between gallstones and ALI by subgroup analysis (OR = 1.43; 95% CI: 1.16–1.76; p for interaction = 0.0204).ConclusionThe study concluded that ALI and gallstones had a positive correlation, with ALI having a higher effect on women’s gallstone prevalence.